Pengaruh Model Inquiry Terbimbing Terhadap Pemahaman Konsep Siswa Pada Materi Ekosistem: Pengaruh Model Inquiry Terbimbing Terhadap Pemahaman Konsep Siswa Pada Materi Ekosistem - Haswan, Haswan; Ridzal, Dewi Asriani; Nurmayanti (Universitas Muslim Buton, 2022)
This study aims to know the influence of the guided inquiry model on the concept understanding of ecosystem material for class X students of SMAN 10 Kendari. kind of this research is quasi-experiment research with the research design being the Nonequivalent Control Group Design. The sampling technique is purposive sampling. The research sample amounted to 52 students who were divided into 2 groups, namely the experimental class group and the control class group. The research instrument used was an objective test in the form of multiple choice (Multiple Choice Item Test). The results of the descriptive analysis show that there is an increase in the value of understanding the concepts taught by the guided inquiry model and direct learning. The increase in the value of understanding the concepts of students who are taught using the guided inquiry model is 32.24 and indirect learning is 27.77. The results of the inferential analysis show that the significance value obtained is 0.014 which is smaller than the alpha value equal to 0.05 so it can be concluded that the application of the guided inquiry model has a positive and significant impact on students' understanding of the concept of ecosystem material.